Ion transport in plant cells under magnetic field - Savchenko, V. (Енергетика і автоматика, 2015)
The influence of magnetic field on ion transport in plant cells. The dependences of changes in the concentration of ions and electrolytic conductivity cell plants of magnetic field parameters.